Increased protective efficacy of recombinant BCG strains expressing virulence-neutral proteins of the ESX-1 secretion system. Issue 23 (28th May 2015) - Bottai, Daria; Frigui, Wafa; Clark, Simon; Rayner, Emma; Zelmer, Andrea; Andreu, Nuria; de Jonge, Marien I.; Bancroft, Gregory J.; Williams, Ann; Brodin, Priscille; Brosch, Roland
Highlights: Single mutations in ESAT-6 attenuate the virulence of BCG::ESX-1 variants. BCG::ESAT-L28A/L29S vaccine combines virulence attenuation and improved protection. Expression of virulence-neutral ESX-1 enhances the protective potential of BCG. Abstract: Background : Mycobacterium bovis BCG is presently the only available anti-tuberculosis vaccine used, worldwide. While BCG protects against miliary tuberculosis (TB) and tuberculoid meningitis in children, it often fails to protect against adult pulmonary TB. It is thus imperative that new improved anti-TB vaccines are developed. The integration of the ESX-1 secretion system, absent from BCG due to the deletion of region of difference 1 (RD1), into the genome of BCG has been shown to confer to BCG::ESX-1 enhanced protection against TB as compared to BCG. Methods : In the present study, to counterbalance the increase in virulence resulting from the integration of the RD1 region into BCG, we have constructed and evaluated several BCG::ESX-1 variants that carry selected amino-acid changes in the ESX-1-secreted antigen ESAT-6. In order to find the candidate that combines low virulence with high protective efficacy, these novel recombinant BCG::ESX-1 strains were tested for their virulence properties and their protective efficacy against Mycobacterium tuberculosis in two different animal models (mouse and guinea-pig). Results : Among several candidates tested, the BCG::ESAT-L28A/L29S strain, carrying modifications at residues Leu 28 -Leu 29 of the ESAT molecule, showed strong attenuation in mice and high protective efficiency both in mouse and guinea-pig vaccination-infection models. Conclusion : This strain thus represents a promising candidate that merits further investigations and development. Our research also provides the proof of concept that selected ESX-1-complemented BCG strains may show low virulence and increased protective potential over parental strains.